The relation between human hair follicle density and touch perception - Jönsson, Emma H. (Sci Rep, 2017)
Unmyelinated low threshold C-tactile fibers moderate pleasant aspects of touch. These fibers respond optimally to stroking stimulation of the skin with slow velocities (1–10 cm/s). Low threshold mechanoreceptors are arranged around hair follicles in rodent skin. If valid also in humans, hair follicle density (HFD) may relate to the perceived pleasantness of stroking tactile stimulation. We conducted two studies that examined the relation between HFD and affective touch perception in humans. In total, 138 healthy volunteers were stroked on the forearm and rated the pleasantness and intensity. Stimulation was performed by a robotic tactile stimulator delivering C-tactile optimal (1, 3, 10 cm/s) and non-optimal (0.1, 0.3, 30 cm/s) stroking velocities. Additionally, a measure of discriminative touch was applied in study 2. HFD of the same forearm was determined using the Cyanoacrylate Skin Stripping Method (CSSM), which we validated in a pretest. Women had higher HFD than men, which was explained by body size and weight. Furthermore, women rated affective touch stimuli as more pleasant and had higher tactile acuity. Depilation did not affect touch perception. A weak relationship was found between the C-tactile specific aspects of affective touch perception and HFD, and the hypothesis of HFD relating to pleasant aspects of stroking only received weak support.